Framing health and foreign policy: lessons for global health diplomacy - Labonté Ronald; Gagnon Michelle L (BMC, 2010)
Abstract Global health financing has increased dramatically in recent years, indicative of a rise in health as a foreign policy issue. Several governments have issued specific foreign policy statements on global health and a new term, global health diplomacy, has been coined to describe the processes by which state and non-state actors engage to position health issues more prominently in foreign policy decision-making. Their ability to do so is important to advancing international cooperation in health. In this paper we review the arguments for health in foreign policy that inform global health diplomacy. These are organized into six policy frames: security, development, global public goods, trade, human rights and ethical/moral reasoning. Each of these frames has implications for how global health as a foreign policy issue is conceptualized. Differing arguments within and between these policy frames, while overlapping, can also be contradictory. This raises an important question about which arguments prevail in actual state decision-making. This question is addressed through an analysis of policy or policy-related documents and academic literature pertinent to each policy framing with some assessment of policy practice. The reference point for this analysis is the explicit goal of improving global health equity. This goal has increasing national traction within national public health discourse and decision-making and, through the Millennium Development Goals and other multilateral reports and declarations, is entering global health policy discussion. Initial findings support conventional international relations theory that most states, even when committed to health as a foreign policy goal, still make decisions primarily on the basis of the 'high politics' of national security and economic material interests. Development, human rights and ethical/moral arguments for global health assistance, the traditional 'low politics' of foreign policy, are present in discourse but do not appear to dominate practice. While political momentum for health as a foreign policy goal persists, the framing of this goal remains a contested issue. The analysis offered in this article may prove helpful to those engaged in global health diplomacy or in efforts to have global governance across a range of sectoral interests pay more attention to health equity impacts.